Additive Manufacturing Plant for Large Scale Production of Medical Devices: A Simulation Study. Issue 11 (2018) - Avventuroso, Giuseppe; Silvestri, Marco; Frazzon, Enzo Morosini
Abstract: The capability of additive manufacturing (AM) to produce one-of-a-kind products makes it suitable to medical and pharmaceutical devices production, enabling the large-scale implementation of the personalized medicine paradigm. In this paper, to support planning, designing, and performance evaluation of an AM plant for large scale production of medical devices for healing chronic wounds, a simulation-based analysis was performed. Obtained results support planning and design decision-making, allowing for a better choice among alternative set-ups, and contribute to the evaluation of potential benefits and economic feasibility of new AM technologies.